PALINOLOGÍA DE LA FORMACIÓN EL IMPERIAL, PALEOZOICO SUPERIOR, CUENCA SAN RAFAEL, REPÚBLICA ARGENTINA. PARTE II: GRANOS DE POLEN, INCERTAE SEDIS, ACRITARCAS. (Ameghiniana, 2014)
"The microfloristic study of the El Imperial Formation, Upper Palaeozoic of the San Rafael Basin, is presented. This second contribution comprises the systematic description of thirty-two species of poli en grains, ten taxa of acritarchs and six species of incertae sedis. Most taxa of poli en grains and incertae sedis have been referred to previously described species, only ten of them are left in open nomenclature. Two species of pollen grains: Limitisporites monosaccoides Bose and Maheshwari and Caheniasaccites elongatus Bose and Kar and another one of incertae sedis: Quadrisporites horridus (Hennelly) Potonié and Lele have been described in Argentina for the first time. One species of poli en grains is here newly combined: Pakhapites ovatus Bose and Kar. Among the acritarchs, only two taxa have been referred to previously established species, whereas the rest has been informally identified because of their paucity. The cuantitative analysis of the palynologicallevels is exposed and the palaeoecological aspects of the different groups are discussed. Two palynological associations are recognized: the Lower Association, correlated with the Raistrickia-Plicatipollenites Subzone of the Lunbiadispora - Potonieisporites Zone, middle Late Carboniferous in age, and the Upper Association, related to the Lower Cristatisporites Zone, regarded as Early Permian."